Control of electron dynamics, radical and metastable species generation in atmospheric pressure RF plasma jets by Voltage Waveform Tailoring - Korolov, I; Donkó, Z; Hübner, G; Bischoff, L; Hartmann, P; Gans, T; Liu, Yue; Mussenbrock, T; Schulze, Julian (Plasma Sources Science and Technology, 2019)
Atmospheric pressure capacitively coupled radio frequency discharges operated in He/N2 mixtures and driven by tailored voltage waveforms are investigated experimentally using a COST microplasma reference jet and by means of kinetic simulations as a function of the reactive gas admixture and the number of consecutive harmonics used to drive the plasma. Pulse-type ‘peaks’-waveforms, that consist of up to four consecutive harmonics of the fundamental frequency ( f=13.56 MHz), are used at a ﬁxed peak-to-peak voltage of 400 V. Based on an excellent agreement between experimental and simulation results with respect to the DC self-bias and the spatio-temporal electron impact excitation dynamics, we demonstrate that Voltage Waveform Tailoring allows for the control of the dynamics of energetic electrons, the electron energy distribution function in distinct spatio-temporal regions of interest, and, thus, the generation of atomic nitrogen as well as helium metastables, which are highly relevant for a variety of technological and biomedical applications. By tuning the number of driving frequencies and the reactive gas admixture, the generation of these important species can be optimised. The behaviour of the DC self-bias, which is different compared to that in low pressure capacitive radio frequency plasmas, is understood based on an analytical model.